Implementasi Pembelajaran Pendidikan Agama Islam (PAI) Membentuk Karakter Siswa Di SMP Queen Al – Falah Ploso Mojo Kediri - Anta Gusnanda; Moh. Irmawan Jauhari; Suko Susilo (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the implementation of Islamic Religious Education PAI in shaping students’ religious character at SMP Queen Al-falah Ploso Mojo Kediri. The background of this research is rooted in the importance of character education as a response to the ongoing moral crisis among students, as well as the strategic role of PAI in instilling religious and moral values. This study employs a descriptive qualitative approach using a phenomenological method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed inductively using source and technique triangulation to ensure data validity. The findings reveal that PAI instruction at SMP Queen Al-Falah is carried out systematically and is integrated with students’ religious activities, such as congregational prayers, Qur’an recitation (tadarus), and other worship practices. PAI teachers actively serve as role models, facilitators, and motivators in shaping students’ character through contextual and participatory learning approaches.Despite challenges such as limited teaching media and diverse student backgrounds, the I mplementation of PAI has had a positive impact on strengthening students’ faith, discipline, sense of responsibility, and social behavior. The school’s religious culture and the supportive pesantren environment further reinforce the internalization of Islamic values in students' daily lives. In conclusion, the study affirms that PAI is not merely religious instruction but serves as a fundamental foundation for character building among the younger generation. It is recommended that PAI teachers continue to develop active and contextual learning methods, and that schools enhance their religious environment as part of a comprehensive effort to support students' character development